Sometimes I think the shack was better : examining flood-risk in subsidised housing areas in Cape Town. - Pharoah, Robyn (Department of Environmental and Geographical Science, 2014)
This thesis examines the extent, nature and impact of flooding in informal and subsidised housing areas on the Cape Flats. Drawing on constructivist arguments regarding the subjectivity of risk as a concept, I examine how flooding and risk are conceptualised locally and internationally, and how well these framings compare with people's experiences in subsidised housing areas in Cape Town. I show that flooding remains a significant challenge in subsidised housing areas. Flood-risk has a strong built environment component; the very dwellings that should help to improve people's lives serve instead to transform and perpetuate risk, undermining the developmental objectives of the housing programme. In so doing, I interrogate assumptions about risk, hazard and vulnerability, and the lessons for theory and practice.